Pembangunan Ekonomi Syariah Berbasis Pemberdayaan Sumber Daya Manusia pada UPT Balai Latihan Kerja Jember - Rodiatul Mafila; Cindi Citra Sari; Margareta Anggun Puspita; Mutmainnah Mutmainnah; Sofiah Sofiah (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to analyze the role of UPT Balai Latihan Kerja (BLK) Jember in human resource empowerment and its contribution to the development of the Islamic economy. This study employs a qualitative approach with a descriptive method to obtain a comprehensive understanding of the implementation of job training programs. Data collection was conducted through observation, in-depth interviews, and documentation by involving institutional managers, instructors, as well as trainees and alumni as the main informants. Data analysis was carried out using an interactive analysis model, which includes data reduction, data display, and systematic conclusion drawing. The results show that the job training programs at UPT BLK Jember play a significant role in improving workers’ skills and competencies, thereby enhancing their competitiveness in the labor market. In addition, these programs contribute to expanding employment opportunities and encouraging economic self-reliance within the community. The training programs are also in line with the principles of Islamic economic development, which emphasize human empowerment as the subject of development and support the achievement of maqasid al-shariah, particularly in improving social welfare in a sustainable manner.